Determinants of Brand Loyalty in Social Media Marketing: The Impact of Influencer Marketing and Content Quality on TikTok Users - Mas Intan Purba; Darwin Lie; Sofiyan Sofiyan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid growth of social media has transformed digital marketing strategies, particularly through TikTok as a platform for fashion product promotion. Influencer marketing and content quality have become important factors that may influence consumer brand loyalty. This study aims to examine the effect of influencer marketing and content quality on brand loyalty among TikTok users who consume fashion products in Medan, Indonesia. This research uses a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 385 active TikTok users in Medan who had experienced fashion product promotions through influencers. The sampling method combined purposive and accidental sampling techniques. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLLS software. The findings indicate that influencer marketing has a positive and significant effect on brand loyalty, with a path coefficient of 0.622, t-statistic of 10.850, and p-value of 0.000. Content quality also has a positive and significant effect, with a path coefficient of 0.189, t-statistic of 3.474, and p-value of 0.001. The R² value of 0.616 shows that influencer marketing and content quality simultaneously explain 61.6% of the variation in brand loyalty. The results highlight that influencer marketing has a stronger influence than content quality in building brand loyalty among fashion consumers on TikTok. Therefore, fashion businesses should focus on collaborating with credible influencers and developing engaging, relevant, and high-quality content to strengthen customer relationships and maintain long-term loyalty.